Design and analysis of dual feed patch antenna at 3.5 GHz mid-band 5G technology. (19th November 2021) - Prabhu, T.; Suganya, E.; Pandian, S. Chenthur
A circularly polarised (CP) patch antenna with dual feed is presented. The antenna consists of a radiating patch, substrate and ground plane. A pair of feed is placed at TM10 and TM01 mode with same amplitude and 900 phase differences. The two orthogonal modes are excited by using coaxial probe feed. By changing the phase difference of two modes, both the left and right hand circularly polarised waves are obtained. The antenna is designed at mid-band 5G technology (i.e., 3.5 GHz) and simulated results obtained with return loss of −25.03 dB, impedance bandwidth of 75 MHz from 3.461 to 3.536 GHz, gain of 7.87 dBic and 3 dB axial ratio bandwidth of 49 MHz from 3.495 to 3.544 GHz. The proposed antenna had been considered as an excellent option for mid band 5G technologies to improve the coverage and capacity benefits.